Single Incision Laparoscopic Assisted Appendectomy: Experience in Paediatric Patients - Shahid, Shah Md Ahsan; Ali, Nawshad; Islam, Sayed Sirajul; Ahmed, Mostaque (Bangladesh Journal of Endosurgery, 2013)
Background: Laparoscopic appendectomy is considered as a superior alternative to open appendectomy. Usual laparoscopic appendectomy is performed with the three port system. In this study, we performed a unique single transumblical incision two-port laparoscopic assisted appendectomy with the aim to reduce postoperative complications as well as improving cosmesis and patients satisfaction. Methods: From January 2010 to December 2011, 136 patients were admitted with clinically diagnosed acute appendicitis and were randomly assigned to single transumblical incision two-port laparoscopic assisted appendectomy. Result: Transumblical single incision two-port laparoscopic assisted appendectomy was attempted in all patients (52 males and 84 females) with an average age of 8.5 years. Transumblical single incision two-port laparoscopic-assisted appendectomy was successfully completed in 134 patients. In two patients, another additional port was required due to sever adhesion of the appendix. Mean operation time was 25.2 min (range, 1738), and mean postoperative hospital stay was 2 days (range 13). Postoperative complications were negligible. Conclusion: Transumblical single incision two-port laparoscopic-assisted appendectomy appears to be a feasible and safe technique for the treatment of acute appendicitis in the paediatric setting. It allows nearly scar less abdominal surgery. DOI: http://dx.doi.org/10.11593/bje.2013.0102.0009 Bangladesh Journal of Endosurgery Vol.1(2) May 2013: 15-19